2014
DOI: 10.1007/s12072-014-9594-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vasopressin/terlipressin and somatostatin/octreotide for the prevention of early variceal rebleeding after the initial control of bleeding: a systematic review and meta-analysis

Abstract: There is no difference between vasopressin/terlipressin and somatostatin/octreotide in prevention of re-bleeding after the initial treatment of bleeding esophageal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
4
20
0
2
Order By: Relevance
“…There is no difference between vasopressin/terlipressin and SSAs in the prevention of re-bleeding after the initial treatment of bleeding esophageal varices [169]. Treatment with SSAs should be started as soon as possible and in conjunction with endoscopic treatment.…”
Section: Acute Bleeding From the Gastrointestinal Tractmentioning
confidence: 99%
“…There is no difference between vasopressin/terlipressin and SSAs in the prevention of re-bleeding after the initial treatment of bleeding esophageal varices [169]. Treatment with SSAs should be started as soon as possible and in conjunction with endoscopic treatment.…”
Section: Acute Bleeding From the Gastrointestinal Tractmentioning
confidence: 99%
“…Although the use of vasoactive agents for the reduction in portal pressure and control of rebleeding specific to gastric variceal bleeding is unavailable in literature, the same line of supportive therapy as for esophageal variceal bleeding, is currently recommended. Wang et al in their systematic review and meta-analysis showed that there was no difference between vasopressin/terlipressin and somatostatin/octreotide in the prevention of re-bleeding after the initial treatment of bleeding esophageal varices [ 30 ]. Antibiotic prophylaxis, lactulose for the prevention of hepatic encephalopathy along with other supportive measures that include varying degrees of organ support depending on the severity of systemic dysfunction is mandated in GV bleed [ 31 ].…”
Section: Treatmentmentioning
confidence: 99%
“…To date, cumulative randomized prospective studies had been carried out to compare the effectiveness of terlipressin and octreotide for the control of acute variceal bleeding 7 , 15 , 17 21 . All of them concluded that the efficiency of terlipressin and octreotide in controlling variceal bleeding was not different in terms of the hemostatic effect, safety, hospital stay, or mortality 15 , 21 .…”
Section: Discussionmentioning
confidence: 99%